Family, Poverty, and Vulnerability: An Analysis of Human Trafficking Prevention Practices in West Java - Hidayat, Eva Nuriyah; Suriadi, Agus (MUHARRIK: Jurnal Dakwah dan Sosial, 2026)
The crime of Trafficking in Persons (TIP) in Indonesia is predominantly understood through the lenses of law enforcement and structural factors such as poverty and irregular migration, whereas mediation mechanisms at the family level during the pre-recruitment phase remain conceptually under-synthesized. This gap results in the fragmentation of prevention approaches, which have yet to fully address risk production at the household level. This study aims to reconstruct a tiered TIP prevention model by positioning family protective literacy as a risk mediator. Employing a qualitative approach based on a targeted literature review, this study conducts a thematic analysis of literature published between 2016 and 2025 concerning vulnerability, migration, social protection, and collaborative governance. The synthesis reveals that structural pressures do not deterministically lead to exploitation; rather, they are mediated by the family's capacity to comprehend safe migration procedures, scrutinize recruitment information, and mitigate financing risks. Legal, digital, and financial literacies function as mediation nodes connecting macro-level pressures with micro-level migration decisions, which are subsequently reinforced or undermined by community and village dynamics, alongside macro-level governance orchestration. Ultimately, this study proposes the Protective Literacy-Based Tiered Prevention Model as a conceptual contribution to bolster preventive approaches within the social welfare system.